Implementasi Analisis dan Mitigasi Risiko Menggunakan Metode House of Risk Pada Laboratorium Kalibrasi PT XYZ - Fuad, Muhammad Shofil; Suryadi, Akmal (Jurnal Serambi Engineering, 2025)
Intense competition in the marketplace encourages every company to continuously maintain and improve the quality of its products. High quality standards are not only a measure of customer confidence, but also an important factor in maintaining competitiveness in the market. This study aims to analyse and mitigate risks in the calibration process at PT XYZ laboratory using the House of Risk (HOR) method. Quality control in the calibration of measuring instruments is very important to ensure that the products manufactured are of a high quality and in compliance with standards. The HOR approach is carried out in two stages. HOR Stage 1 to identify and prioritise risk agents based on the Aggregate Risk Potentials (ARP) value, and HOR Stage 2 to formulate effective mitigation strategies. The results showed 13 dominant risk agents out of a total of 22 identified, with mitigation prioritised based on effectiveness scores and difficulty of implementation. Suggested mitigation strategies include clear tool identification, skills training, ergonomic layout, task rotation, standard waste management, document digitisation, workspace optimisation and improved communication and team coordination to support efficiency and safety. This research is expected to help companies manage risk, improve the efficiency of the calibration process and maintain the quality of measurement results in accordance with established standards. This research is expected to help the company manage risk, improve the efficiency of the calibration process and maintain the quality of measurement results in accordance with established standards.